Investigation of geometric uncertainties in ig-imrt of head and neck cases - Mansor, Mohamad Hussin (Universiti Sains Malaysia, 2016)
The purpose of this study was to investigate the geometric uncertainties in IG-IMRT of head and neck cancer cases that treated at the radiotherapy of Advance Medical and Dental Institute, AMDI. In estimation the set-up error for Linear Accelerator ( LINAC) in radiotherapy department, a weekly Quality Assurance (QA) for Image Guide (IG) also known as XVI system. This QA was determine the error in translation magnitude in lateral (X) axis, longitudinal (Y) axis and vertical (Z) axis. Image data acquisition from patient treated of IG-IMRT at the radiotherapy department during the period 2015 until 2016 was used to estimate the set-up displacements for each treatment area. By using the acquired images the magnitude of error was determined in the lateral (X) axis, longitudinal (Y), and vertical (Z) axis. The calculated PTV margin based on the systematic error and random error entire patient populations. A total 6 patients were used for the retrospective analysis of head and neck cancer treatments. Image data acquisition from the experiment of iCAST mask thermoplastic molded at the ART head and neck phantom was used to estimate the set-up displacement. By using the acquired images the magnitude error was determined in the lateral (X) axis, longitudinal (Y), and vertical (Z) axis. The calculated PTV margin based on the systematic and random error. The evaluation of the displacement and PTV margin was done for 3 different condition of the iCAST mask thermoplastic; new, 1st remold and 2nd remold. Measurement of the iCAST mask thermoplastic to estimate the amount the shrinkage stretch of the iCAST mask thermoplastic. By using the 2 method to measuring the shrinkage stretch of thermoplastic mask; molding at the ART head and neck phantom shape and flatted shape. The evaluation of the shrinkage stretch of thermoplastic mask was done in three different condition of the iCAST mask thermoplastic; new, 1st remold, and 2nd remold. The deviation for all test conducted during the QA of the IG-IMRT system within the tolerance ±1.0 mm. The maximum of the error -0.1 mm for lateral (X), -0.3 mm for longitudinal (Y), and -0.7 mm for vertical (Z). The corresponding PTV margin in head and neck cancer cases was found 3.6mm in lateral (X), 5.1 mm in longitudinal (Y), and 5.3 mm in vertical (Z) axis. The maximum displacement -3.0 mm for lateral (X), 4.9 mm for longitudinal (Y), and 4.7 mm for vertical (Z). PTV margin iCAST mask thermoplastic phantom was found 1.1 mm in lateral (X), 2.0 mm in longitudinal (Y), and 5 mm in vertical (Z) axis. The maximum displacement -1.2 mm for lateral (X), 1.7 mm for longitudinal (Y), and -1.8 mm for vertical (Z). Total maximum shrinkage of iCAST mask thermoplastic by laser and diameter measurement by the molding at the ART head and neck phantom are 2.11% and 1.24% and by the flatted shape iCAST mask thermoplastic are 1.27%. The current study was determine the geometric uncertainties for HNC cases, by combination of the QA measure the setup error in the system machine and also retrospective patient HNC treated by the IG-IMRT for measure error in displacement setup for positioning during the treatment. This study also determine the effect of reusable thermoplastic mask to HNC patient for treatment of IG-IMRT by measure the total displacement from it. Addition, whether the condition of the thermoplastic show the total shrinkage stretch of the thermoplastic in different value but acceptable to used reusable thermoplastic for treat patient HNC.